Drainage-Improved Sediment Strength Enhances Saltmarsh Seedling Establishment Chance - Cao, Haobing; Zhu, Zhenchang; Hu, Zhan; Wang, Heng; Bouma, Tjeerd J. (Frontiers in Marine Science, 2022)
Identify critical factors driving seedling establishment is essential for saltmarsh restoration. Recent studies highlight drainage can facilitate seedling establishment for different saltmarsh species, yet the underling mechanism remains largely unknown. By a manipulative mesocosm experiment with contrasting sediment drainage treatments, we investigated the impacts of drainage on Spartina anglica seedlings survival, growth and stability. Surprisingly, neither S. anglica seedling survival nor seedling growth were observed to be directly promoted by well drained treatment. However, the critical erosion depth (maximum erosion tolerance) of S. anglica seedlings was found to positively correlate with seedling root length. Measurements on the sediment properties revealed that drainage increased the critical shear strength of sediments with lower water content and higher dry bulk density. These findings indicate that, by dewatering, drainage aids to sediment consolidation and critical shear strength, and thereby facilitate seedling establishment in tempering sediment dynamics. The latter is supported by a field study, in which we found that the magnitude of the sediment dynamics on two tidal flats were positively related to water content of sediment. Overall, present study suggests that drainage could be a key factor that determines seedling stability during the critical windows of opportunity for seedling establishment, and that it could be integrated into future designs for saltmarsh restoration to enhance establishment success.